Pemikiran Hermeneutika Khaled M. Abou El Fadl: Dari Fikih Otoriter Ke Fikih Otoritatif - M Taufiq; Muhammad Ilham (Universitas Islam Negeri Sumatera Utara, 2021)
Artikel ini merupakan analisis buku yang ditulis Khaled M. Abou el-Fadl berjudul Speaking in God’s Name: Islamic law, Authority and Women, yang mencoba memaparkan pemikiran Khaled M. Abou El Fadl yang mengusung teori otoritas dengan menggunakan pendekatan hermeneutika sebagai pisau analisis dalam menyikapi persoalan hukum Islam yang berkembang selama ini yang masih dianggap diskriminatif, dalam istilah Khaled M. Abou El Fadl disebut sebagai otoritarianisme interpretasi. Hermeneutika yang Khaled M. Abou El Fadl kembangkan berorientasi pada otoritas penafsiran sebuah teks dengan menegosiasikan teks, pengarang dan pembaca dengan memperhatikan tiga hal, yaitu; kompetensi (autentisitas), penetapan makna, dan perwakilan. Tiga pokok persoalan inilah menurut Khaled M. Abou El Fadl, memainkan peranan penting dalam membentuk pemegang otoritas dalam dikursus keislaman. This article is an analysis of the book written by Khaled M. Abou el-Fadl entitled Speaking in God's Name: Islamic law, Authority and Women, which tries to explain the thoughts of Khaled M. Abou El Fadl who carries the theory of authority by using a hermeneutic approach as an analytical knife in addressing The problems of Islamic law that have developed so far are still considered discriminatory, in Khaled M. Abou El Fadl's terms referred to as interpretation authoritarianism. The hermeneutics that Khaled M. Abou El Fadl developed is oriented towards the authority of the interpretation of a text by negotiating the text, the author and the reader by paying attention to three things, namely; competence (authenticity), determination of meaning, and representation. According to Khaled M. Abou El Fadl, these three main issues play an important role in shaping the authority holders in Islamic discourse.